Bridging the Transition from Pre-Service Teaching to Classroom Practice: A Phenomenological Study of Professional Identity Formation, Adaptation, and Resilience among Future Educators in Philippine Basic Education - Rosemelita Valdez-Bastian, (The Bioscan, 2026)
The transition from pre-service teacher preparation to actual classroom practice represents a critical developmental stage in teacher education. During this period, future educators encounter authentic teaching experiences that challenge their pedagogical knowledge, professional dispositions, and personal resilience. This phenomenological study explored the lived experiences of Isabela State University pre-service teachers deployed in selected public elementary schools in Echague, Isabela, namely Echague East Central School, Echague West Central School, Echague South Central School, and Soyung Elementary School. Guided by Professional Identity Theory and Experiential Learning Theory, the study examined how pre- service teachers constructed their professional identities, adapted to classroom realities, and developed resilience during field deployment. Using purposive sampling, twenty pre-service teachers participated in in-depth interviews and reflective journaling. Data were analyzed through thematic analysis. Findings revealed that deployment served as a transformative process characterized by confronting classroom realities, adapting instructional practices, negotiating professional identity through mentorship, cultivating emotional resilience, and strengthening commitment to the teaching profession. The study highlights the importance of structured mentoring, reflective practice, and institutional support in facilitating successful transitions from teacher preparation programs to professional practice. The findings contribute to the growing literature on teacher education and offer implications for enhancing field-study and internship programs in Philippine higher education institutions.